Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif Student Teams Achievement Division (STAD) - Novi Marliani; Ambarsari; Idha Isnaningrum (CV Putra Publisher, 2023)
The aim of this research is to determine whether the application of Student Teams Achievement Divisions (STAD) cooperative learning can improve learning outcomes. This research was carried out at SMA Martia Bhakti Bekasi Jl. Jendral Sudirman Km. 32 Kayuringin Jaya Village, South Bekasi District, Bekasi City. In this research, the samples to be taken are class X.2 as an experiment with a total of 35 students, and class X.3 as a control class with a total of 35 students. So the total sample used was 70 students. The cooperative learning model requires students' skills and cooperation in their groups, training students in critical thinking so that students' ability to understand the subject matter presented can increase. Meanwhile, researchers chose STAD cooperative learning because STAD cooperative learning is the simplest cooperative learning and easiest to apply in classes that have never implemented cooperative learning. Thus, it can be concluded that providing the Student Team Achievement Division (STAD) type cooperative learning model has a positive effect on mathematics learning outcomes on the subject of Mathematical Logic. From the research results, it can be concluded that providing the Student Team Achievement Division (STAD) type cooperative learning model has a positive effect on mathematics learning outcomes on the subject of Mathematical Logic.